Implementasi Konseling Lintas Agama Dan Budaya Dalam Mewujudkan Toleransi Beragama - Muh. Azhar Mubarak, Azhar (BKI IAIN Pontianak, 2023)
Abstract: Community problems are more complex if there is a relationship between religion and culture. Various problems occur in society caused by religious and cultural biases. Thus affecting a person's psyche, which has an effect on a lack of tolerance in religion. To avoid various possibilities that will occur, the concept of interfaith and cultural counseling was created to reduce the various biases that will occur. This study used a descriptive qualitative method with a library research approach, which was obtained through searching for journal articles based on online media. The results found that cross-religious and cultural counseling can create religious tolerance in the community by using an eclectic counseling approach, an eclectic counseling approach is able to combine various counseling concepts so that they are flexible and can realize religious tolerance in the community.